The Stakeholder’s Role in Education for Sustainable Development at Marine Protected Area - West Kalimantan - Utami, Pratita Budi; Yuliastuti, Indah; Sunardi, Sunardi; Agung, Medha Pradipta; Dwihastuty, Leny; Auliansyah, Auliansyah; Rudianto, Arif; Zulfian, Zulfian; Ilyas, Nail Radhy; Triningsih, Endang; Multazam, Multazam; Kusumardana, Setra; Hartono, Hartono; Purnama, Freddy Surya; Apriansyah, Apriansyah; Kushadiwijayanto, Arie Antasari; Zibar, Zan; Raynaldo, Adityo; Triyono, Triyono; Yusuf, Muhammad; Isharianto, Isharianto; Vietsaman, Dionisius Endy; Nursalam, Lodri Khairul (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2025)
West Kalimantan Province has five Marine Protected Areas (MPAs), one of which is the Randayan MPA. It is located in Bengkayang Regency abd was officially established in 2019 through Peraturan Daerah Provinsi Kalimantan Barat No. 1. One of the mandated activities was public education on conservation, which mostly targeted adults whose livelihoods depended on the extraction of natural resources. Concerning the conservation awareness gap for teenagers and children, our Program Kreativitas Mahasiswa (PKM) initiated the application of the concepts of Social Capital and Bandura’s Social Learning Theory to facilitate this the community. It was found that the involvement of multi stakeholders supports the well-rounded learning experience for the children and teenagers in enchancing their awareness about the conservation of marine ecosystem and the life of under water. Online guest lecture from Ministry of Marine Affairs and Fisheries as well as guided learning process by undergraduate students through their community service program are some of the influential initiatives.